2017
DOI: 10.1111/eth.12582
|View full text |Cite
|
Sign up to set email alerts
|

In Space and Time: Territorial Animals are Attracted to Conspecific Chemical Cues

Abstract: Territorial animals lay scent marks around their territories to broadcast their presence, but these olfactory signals can both attract and repel con-specifics. Attraction or aversion can have a profound impact in terms of space use and thereby influence an individual’s access to resources and mates. Here, we test the impact of chemical signals on the long-term space use and activity of receivers, comparing the response of males and females, territory holders, and temporary visitors in Sceloporus undulatus liza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Conspecifics chemical scents recognition is present in other Liolaemus species (Labra, 2008) and is common in other lizard genera (e.g., Cordylus, Cooper, van Wyk and Mouton, 1996;Podarcis, López and Martín, 2001;Psammodromus, Martín and López, 2006). Scent deposition and conspecific recognition are important for territorial interactions among lizards (Mason and Parker, 2010;Campos, Strauss and Martins, 2017). Inversely, L. albiceps performed few visual displays, in accordance with the observations of Bozzo Miranda (2014) on L. chiliensis, a Liolaemus lizard with pores in both sexes.…”
Section: Discussionsupporting
confidence: 85%
“…Conspecifics chemical scents recognition is present in other Liolaemus species (Labra, 2008) and is common in other lizard genera (e.g., Cordylus, Cooper, van Wyk and Mouton, 1996;Podarcis, López and Martín, 2001;Psammodromus, Martín and López, 2006). Scent deposition and conspecific recognition are important for territorial interactions among lizards (Mason and Parker, 2010;Campos, Strauss and Martins, 2017). Inversely, L. albiceps performed few visual displays, in accordance with the observations of Bozzo Miranda (2014) on L. chiliensis, a Liolaemus lizard with pores in both sexes.…”
Section: Discussionsupporting
confidence: 85%
“…Future research should investigate other nuances of chemoreception and chemical stimuli, and their use in chemosensory enrichment. For example, previous studies have shown that some species of reptiles can gather information of territory ownership or assess the quality of territories based on conspecific cues, and that they are attracted to the latter (e.g., Campos, Strauss, & Martins, ; Carazo et al, ; Carazo et al, ; Stamps, ). It would be interesting to study the use of this type of stimuli (i.e., male conspecific's scents) in other territorial species of squamata.…”
Section: Discussionmentioning
confidence: 99%
“…Sceloporus species use femoral pore secretions for chemical signalling (e.g. Campos, Strauss, & Martins, ; Pruett et al., ), which may provide redundant information to belly colour patches. Chemical signals may also be used more often in species without coloured belly patches, as in S. virgatus , which seems to rely heavily on chemical signals (Hews & Benard, ; Hews, Date, Hara, & Castellano, ).…”
Section: Discussionmentioning
confidence: 99%